An Upgraded Smartphone-Based Program for Leisure and Communication of People With Intellectual and Other Disabilities - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Perilli, Viviana; Chiariello, Valeria; Buono, Serafino (Frontiers in Public Health, 2018)
Background: People with intellectual disability and sensory or sensory-motor impairments may display serious problems in managing functional daily activities as well as leisure activities and communication with distant partners. Aim: The study assessed an upgraded smartphone-based program to foster independent leisure and communication activity of eight participants with mild to moderate intellectual disability, sensory or sensory-motor impairments, and limited speech skills. Method: The upgraded program was based on the use of (a) a Samsung Galaxy A3 smartphone with Android 6.0 Operating System, near-field communication, music and video player functions, and Macrodroid application, and (b) special radio frequency-code labels. Participants requested leisure and communication activities by placing mini objects or pictures representing those activities and containing frequency-code labels on the smartphone. The smartphone, via the Macrodroid application, read the labels (i.e., discriminated the participants' requests) and provided the participants with the activities requested. Results: During the baseline (i.e., in the absence of the program), the participants failed to request/access leisure and communication activities independently. During the post-intervention phase of the study (i.e., using the program), they succeeded in requesting/accessing those activities independently and spent about 70–90% of their session time busy with those activities. Conclusion: The upgraded smartphone-based program may be highly functional for people like the participants of this study.